Evaluación de la técnica de aplicación de la vacuna BCG asociado a la presencia de reacciones adversas. Centro de Salud n°1. Riobamba. Periodo enero-abril 2023 - Bonilla Carvajal, Alexis Gabriel (2023)
The BCG vaccine is one of the first vaccines to be applied to comply with the national immunization scheme, the responsibility of which is under the responsibility of nursing professionals, therefore, mastery of a correct intradermal technique is required for its administration. Although it is one of the safest vaccines, it is not exempt from generating adverse reactions in the population. Objective: To evaluate the BCG vaccine application technique associated with the presence of adverse reactions. Methodology: Type of study: descriptive, correlational, cross-sectional, field; population 8 graduates, 2 nursing interns and 31 representatives of children who were immunized with the BCG vaccine at Health Center No. 1; Two instruments were applied: "observation guide for the application of the BCG vaccine" and "survey to inquire about the possible adverse effects presented post-vaccination in the infant population immunized with the BCG vaccine" which were validated by professionals in the area. Results: 20% of the nursing staff do not provide timely information on the procedure, reactions and post-vaccination care, 20% do not comply with the 10 correct ones, 40% do not disinfect or wash their hands before the procedure, 20% do not prepare the necessary material, 30% do not place the patient in an adequate position to carry out the procedure, 30% fail to comply with the parameters of intradermal administration, 20% do not perform an adequate classification of sanitary waste, 60% do not perform disinfection or post vaccination hand washing. It has been found that the most frequent adverse reactions were: 9.7% large pustule, 3.2% keloid scar, 12.9% pain at the puncture site, 3.2% fever. Conclusion: There is a relationship between the BCG vaccine application technique and the adverse reactions presented in immunized patients. Keywords: BCG vaccine (D001500), adverse reactions (D016907), application technique (D014611), immunization (D007115), intradermal route (D004333